Improving the production quality, promotion and sales of rempeyek initomas in covid-19 era - Ulung Pribadi; Juhari; Rossi Maunofa Widayat (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
"Peyek Initomas," as a micro, small and medium enterprise (UMKM) in Kluwih Sub-Village, has decreased its income since the spread of the COVID19 pandemic. In addition, the small business also packs products that are too simple so that they are less attractive to consumers. Furthermore, the small business does not yet have a wide marketing and packaging label. UMY staff have several program activities to handle the difficulties in partnership with Student Real Work Lectures (KKN). First, the team socialized and trained small business owners to use social media for marketing their products. Second, the team assisted the small businessman in creating location points on Google Maps so that buyers, especially those outside the area, could easily find them. Third, the team assists the business owner in creating a "market place," including Instagram, Shopee, and the Balecatur Website to market their various products